The Development of Website-Based Physics Test Instrument for Senior High School - Ahmad Minanur Rohim; Siti Wahyuni; Susilo Susilo (Universitas Lambung Mangkurat, 2020)
Implementation using a written test and answering in writing requires a lot of time in the correction process, so that in submitting the test results you have to wait quite a long time, the risk of fraud is high. So the product is developed as an alternative media for this problem besides the existing internet media. This study developed a website-based physics test instrument product and obtained information about its feasibility. Products are used in physics learning in high schools as a system that facilitates the process of implementing tests and their assessments. This research design is 4-D development. The results of the validators' assessment of 2 material experts and 2 media experts with CVR, namely 1 and CVI, namely 0.1, were categorized as very good and the feasibility percentage was 89%. as well as a limited trial of 40 respondents, namely 2 teachers and 38 students in one of the public Madrasah Aliyah at Jepara city stated that they agreed with the calculation of the CVR value of 1 and the CVI value of 0.1 which was categorized as very good. Based on the results of the analysis and discussion, it can be concluded that the product being developed is categorized as feasible.